Method for preparing nitrogen-doped molybdenum diselenide-coated carbon hollow spheres and application thereof
Patent Information
- Application Number
- CN202410672266.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-28
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-05-28
AI Technical Summary
[0004]本发明的目的在于提供一种制备氮掺杂二硒化钼包覆碳空心球的方法及应用,以解决上述背景技术中提出的现阶段的锂离子电池电极材料很难有效降低其制备成本,还需利用模板、表面活性剂及复杂设备来制备电极材料,使得电极材料的制备过程较为繁杂,很难适用于大规模工业化生产等问题
1.本发明采用溶液A、溶液B及溶液C之间相互混合的设置,使氮掺杂二硒化钼包覆碳空心球的制备条件更加温和,有利于黑色前驱体的形成,提升了氮掺杂二硒化钼包覆碳空心球制备的效果,从而保证了氮掺杂二硒化钼包覆碳空心球的成品率,通过水热反应及高温煅烧的制备工艺,使氮掺杂二硒化钼包覆碳空心球的制备更加简便快捷,有效地提升了氮掺杂二硒化钼包覆碳空心球制备的效率,从而使氮掺杂二硒化钼包覆碳空心球的制备成本得到了有效地降低,有效地避免了因利用表面活性剂、模板及复杂设备而导致制备过程繁杂的问题,适用于大规模工业化生产,保证了氮掺杂二硒化钼包覆碳空心球的量产化;
Smart Images

Figure CN118637567B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of electrode material preparation and energy storage, specifically relating to a method for preparing nitrogen-doped molybdenum diselenide-coated carbon hollow spheres and its application. Background Technology
[0002] Electrode materials must possess good conductivity, low loss, ease of shaping, good processing stability, high efficiency, abundant material sources, and low cost. Commonly used electrode materials include pure copper, graphite, brass, steel, cast iron, and tungsten alloys. In a battery, the electrode generally refers to the location where the redox reaction occurs with the electrolyte solution. Lithium-ion batteries are widely used in many fields due to their high energy density, environmental friendliness, and flexible design. Traditional lithium-ion batteries use graphite as the anode material. However, its theoretical specific capacity is low, failing to meet the demands for battery energy and power density. Furthermore, graphite's low operating voltage poses significant safety hazards during lithium-ion battery operation. To address the problems associated with graphite anode materials, lithium-ion batteries now use transition metal chalcogenides, such as molybdenum disulfide or molybdenum diselenide, as electrode materials. While transition metal chalcogenides offer advantages such as high capacity, low toxicity, high natural abundance, and environmental friendliness, their extremely low electronic conductivity leads to poor rate performance, and large volume expansion causes rapid capacity decay.
[0003] Existing technologies include research addressing the problems of using molybdenum diselenide as an electrode material for lithium-ion batteries. Examples include patent applications CN115207305A (a method for preparing a molybdenum diselenide-encapsulated nitrogen-doped carbon nanotube composite material and its lithium-ion battery anode material), CN112897479A (a porous carbon-supported MoSe2 electrode material and its preparation method for lithium-ion batteries), and CN109473634A (a method for solid-state co-thermal synthesis of molybdenum diselenide / nitrogen-doped carbon rods). These methods utilize the synergistic effect of hierarchical hollow tubular structures and MoSe2 nanosheets, or... The reaction of sodium with piperazine yields nitrogen-doped starch-based porous carbon materials or covalently bonded composite hierarchical sheet-rod structures, which improves the lithium storage performance of electrode materials. This solves the problems of poor rate performance and rapid capacity decay that exist when molybdenum diselenide is used as an electrode material for lithium-ion batteries. However, existing electrode materials can only guarantee the relevant performance of lithium-ion batteries, but it is difficult to effectively reduce the preparation cost. Templates, surfactants and complex equipment are still required to prepare electrode materials, making the preparation process of electrode materials more complicated and difficult to apply to large-scale industrial production. Summary of the Invention
[0004] The purpose of this invention is to provide a method and application for preparing nitrogen-doped molybdenum diselenide-coated carbon hollow spheres, in order to solve the problems mentioned in the background art, such as the difficulty in effectively reducing the preparation cost of current lithium-ion battery electrode materials, the need to use templates, surfactants and complex equipment to prepare electrode materials, which makes the preparation process of electrode materials more complicated and difficult to apply to large-scale industrial production.
[0005] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing nitrogen-doped molybdenum diselenide-coated carbon hollow spheres, comprising the following specific preparation steps: S1. Dissolve vitamin C and an organic molybdenum source in deionized water to form solution A, wherein the organic molybdenum source is molybdenum acetylacetonate; S2. Add an alkylamine to solution A obtained in S1 and mix to form solution B, wherein the alkylamine is either ethylenediamine or triethylamine; S3. At the same time, sodium selenite is dissolved in hydrazine hydrate to form solution C, wherein the molar ratio of sodium selenite to organic molybdenum source is 2:1. S4. Add solution C obtained in S3 dropwise to solution B obtained in S2 and stir for 20 to 40 minutes to form a mixture. Then transfer the mixture to a hydrothermal reactor at 200 to 250°C and carry out a hydrothermal reaction for 10 to 14 hours. S5. After the hydrothermal reaction is complete, the product is naturally cooled to room temperature to obtain the hydrothermal product. The hydrothermal product is centrifuged, washed and dried to obtain a black precursor. The centrifugation speed is 5000-8000 rpm; the washing is done by first washing with water and then washing with ethanol; the drying temperature is 50-80℃. S6. Place the black precursor obtained in S5 into a crucible and place it in the center of a tube furnace with a heating rate of 5-10℃ / min. Hold it at this temperature for 1.5-2.5 hours. Under an inert atmosphere, first calcine it at a high temperature of 500-800℃, and then cool it to room temperature to obtain black nitrogen-doped molybdenum diselenide-coated carbon hollow spheres. The inert gas is either nitrogen or argon.
[0006] In addition to the above technical solutions, the nitrogen-doped molybdenum diselenide-coated carbon hollow spheres prepared above can also be applied to 2016-type coin cells. The electrodes of the 2016-type coin cells are composed of the following components by mass percentage: 70% nitrogen-doped molybdenum diselenide-coated carbon hollow spheres, 20% super-P and 10% polyvinylidene fluoride.
[0007] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention employs a mixing configuration between solutions A, B, and C, resulting in milder preparation conditions for nitrogen-doped molybdenum diselenide-coated carbon hollow spheres. This facilitates the formation of a black precursor, improves the preparation efficiency of nitrogen-doped molybdenum diselenide-coated carbon hollow spheres, and ensures a high yield. The hydrothermal reaction and high-temperature calcination process further simplifies and accelerates the preparation of nitrogen-doped molybdenum diselenide-coated carbon hollow spheres, effectively increasing the preparation efficiency and reducing the cost. It also avoids the complexities associated with surfactants, templates, and sophisticated equipment, making it suitable for large-scale industrial production and ensuring the mass production of nitrogen-doped molybdenum diselenide-coated carbon hollow spheres. 2. In this invention, solution A prepared from vitamin C and an organic molybdenum source is mixed with alkylamine to form solution B, which is then mixed with solution C formed from sodium selenite and hydrazine hydrate. After hydrothermal reaction and high-temperature calcination, nitrogen-doped molybdenum diselenide-coated carbon hollow spheres are produced. This gives the nitrogen-doped molybdenum diselenide-coated carbon hollow spheres a rich porous structure, which is beneficial for electrolyte wetting and lithium ion diffusion. By utilizing the storage and buffering space of the hollow spheres, the electrodes of the lithium-ion battery can resist stress during continuous charge and discharge, thereby enabling the lithium-ion battery to obtain high specific capacity and good cycle life. 3. The present invention forms a hollow structure by wrapping nitrogen-doped molybdenum diselenide around a carbon hollow sphere, which provides storage and buffer space, facilitates electrolyte wetting and lithium ion diffusion, thereby enabling the lithium-ion battery electrode to resist stress during continuous charging and discharging, ensuring that the lithium-ion battery can achieve high specific capacity and good cycle life. 4. In the nitrogen-doped molybdenum diselenide-coated carbon hollow spheres prepared by this invention, the presence of nitrogen is beneficial to increasing the number of electrochemical active sites, effectively improving the specific capacity and kinetic performance of the electrode. The presence of carbon is beneficial to increasing the conductivity of the electrode, effectively improving the rate performance of the electrode. Thus, the nitrogen-doped molybdenum diselenide-coated carbon hollow spheres exhibit large specific capacity, good rate performance and excellent cycle stability, thereby ensuring the broad application prospects of lithium-ion battery anode materials. Attached Figure Description
[0008] Figure 1 The image shows the XRD pattern of nitrogen-doped molybdenum diselenide-coated carbon hollow spheres from Example 1. Figure 2 The lithium-ion battery assembled with the nitrogen-doped molybdenum diselenide-coated carbon hollow sphere electrode of Example 1 is shown as the CV curve at a scan rate of 0.1 mV / s. Figure 3 The image shows the EIS spectrum of the lithium-ion battery assembled with the nitrogen-doped molybdenum diselenide-coated carbon hollow sphere electrode of Example 1. Figure 4 The GCD curves of the lithium-ion battery assembled with nitrogen-doped molybdenum diselenide-coated carbon hollow sphere electrode in Example 1 are shown at different current densities. Figure 5 The graph shows the cycling performance of the lithium-ion battery assembled with the nitrogen-doped molybdenum diselenide-coated carbon hollow sphere electrode of Example 1 at a current density of 100 mA / g. Figure 6 The image shows the GCD curves of the lithium-ion battery assembled with the nitrogen-doped molybdenum diselenide-coated carbon hollow sphere electrode of Example 5 at different cycles at a current density of 1000 mA / g. Detailed Implementation
[0009] The following examples are used to further illustrate the content of the present invention and do not limit the application of the present invention. Example 1:
[0010] This embodiment provides a method for preparing nitrogen-doped molybdenum diselenide-coated carbon hollow spheres and its application. First, nitrogen-doped molybdenum diselenide-coated carbon hollow spheres need to be prepared. The specific preparation steps are as follows: First, 1.0 g of vitamin C and 0.6523 g of molybdenum acetylacetonate were dissolved in 20.0 mL of deionized water under stirring to form solution A. Next, solution A was added to 5.0 mL of triethylamine and stirred until homogeneous, forming solution B. Simultaneously, 0.6918 g of sodium selenite was dissolved in 10.0 mL of hydrazine hydrate under stirring to form solution C. Then, solution C was added dropwise to solution B and stirred for 30 minutes to form a mixture. This mixture was then transferred to a 50 mL hydrothermal reactor and subjected to a hydrothermal reaction at 200°C for 12 hours. After the hydrothermal reaction is complete, the product is naturally cooled to room temperature to obtain the hydrothermal product. The obtained hydrothermal product is then centrifuged at a speed of 5000-8000 rpm, washed with water and ethanol successively, and then vacuum dried at 60°C to obtain a black precursor. Finally, the obtained black precursor is placed in a crucible and placed in the center of a tube furnace. Under an argon atmosphere, the temperature is raised to 800°C at a heating rate of 5°C / min for high-temperature calcination, held for 2 hours, and then cooled to room temperature under an argon atmosphere to obtain black nitrogen-doped molybdenum diselenide-coated carbon hollow spheres. Secondly, the black nitrogen-doped molybdenum diselenide-coated carbon hollow spheres prepared above were used as electroactive materials in a 2016-type coin cell (one type of lithium-ion battery). The specific steps for assembly and performance testing are as follows: First, the nitrogen-doped molybdenum diselenide-coated carbon hollow spheres were ground into powder. Super-P (conductive carbon black) and polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 70:20:10. Then, 70% of the weighed nitrogen-doped molybdenum diselenide-coated carbon hollow sphere powder, 20% Super-P, and 10% PVDF were added to N-methylpyrrolidone to prepare a slurry, which was then uniformly coated onto copper foil. After drying, it was placed in a vacuum drying oven and cut into pieces with a diameter of 12 mm. A 2016 coin cell was obtained by encapsulating a 1 mm diameter circular electrode as the working electrode in an argon-atmosphere glove box with a nitrogen-doped molybdenum diselenide-coated carbon hollow sphere electrode as the working electrode, a lithium sheet as the counter electrode, and a 1:1:1 mixture of EC (ethylene carbonate), DEC (diethyl carbonate), and DMC (dimethyl carbonate) as the electrolyte. Finally, the energy storage performance of the 2016 coin cell was tested using a supercapacitor (supercapacitor testing includes three aspects: CV (cyclic voltammetry), GCD (galvanostatic discharge), and EIS (electrochemical impedance spectroscopy)). CV and EIS tests were performed on a CHI 760E (dual potentiostat) electrochemical workstation, while GCD tests were performed on a LAHE battery tester. The operating voltage range for CV and GCD tests was 0.01–3.00 V (vs. Li+ / Li), and EIS was tested at open-circuit potential.
[0011] Please see Figures 1-5 , Figure 1 This is the XRD pattern of nitrogen-doped molybdenum diselenide-coated carbon hollow spheres in this embodiment. Figure 1 It can be seen that the strong diffraction peaks of the sample can all be attributed to the 2H phase (hexagonal phase) molybdenum diselenide (MoSe2, such as JCPDS No. 29-0914). There is a weak broad peak near 20°, indicating that the carbon in the nitrogen-doped molybdenum diselenide-coated carbon hollow spheres mainly exists in the form of amorphous carbon. Figure 2 This is the CV curve of the lithium-ion battery assembled with nitrogen-doped molybdenum diselenide-coated carbon hollow sphere electrodes in this embodiment at a scan rate of 0.1 mV / s. Figure 2 It can be seen that there are two obvious redox peaks on the CV curve, indicating that the nitrogen-doped molybdenum diselenide-coated carbon hollow sphere electrode has abundant redox reactions; Figure 3 This is the EIS spectrum of the lithium-ion battery assembled with nitrogen-doped molybdenum diselenide-coated carbon hollow sphere electrodes in this embodiment. Figure 3It can be seen that the EIS spectrum consists of an arc in the high-frequency region and a straight line in the low-frequency region. The intercept of the arc in the high-frequency region on the real axis is about 3.1, indicating that the assembled battery has a small internal resistance. The small diameter of the arc indicates that the electrode has a small charge transfer resistance. The straight line in the low-frequency region is approximately perpendicular to the real axis, indicating that the electrode has excellent lithium-ion diffusion performance. Figure 4 This is a GCD curve of the lithium-ion battery assembled with nitrogen-doped molybdenum diselenide-coated carbon hollow sphere electrodes in this embodiment at different current densities. Figure 4 It can be seen that there are obvious charge and discharge plateaus on each GCD curve, which indicates that there is obvious lithium-ion intercalation / deintercalation behavior during the charge and discharge process. In addition, at current densities of 100, 200, 500, and 1000 mA / g, the discharge specific capacities are 1195.8, 924.7, 809.1, and 749.3 mAh / g, respectively, which indicates that nitrogen-doped molybdenum diselenide-coated carbon hollow spheres have excellent lithium storage performance. Figure 5 The cycling performance of the lithium-ion battery assembled with nitrogen-doped molybdenum diselenide-coated carbon hollow sphere electrodes in this embodiment at a current density of 100 mA / g is given by... Figure 5 It can be seen that from the 2nd to the 10th cycle, the discharge specific capacity decreased from 770.7 mAh / g to 663.7 mAh / g, with an average decrease of 11.9 mAh / g per cycle, indicating that the battery has relatively stable cycle performance. Example 2:
[0012] In this embodiment, the preparation process of nitrogen-doped molybdenum diselenide-coated carbon hollow spheres is the same as that in Example 1, except that the choice of alkylamine and the calcination temperature are different. Specifically, 5.0 mL of ethylenediamine is mixed with solution A to form solution B; under an argon atmosphere, the temperature is raised to 500 °C at a heating rate of 5 °C / min for high-temperature calcination, and then cooled to room temperature to obtain black nitrogen-doped molybdenum diselenide-coated carbon hollow spheres. Similarly, the black nitrogen-doped molybdenum diselenide-coated carbon hollow spheres prepared in this embodiment are used as electroactive materials in 2016-type button batteries (one type of lithium-ion battery), and the assembly and performance testing methods are the same as in Example 1. Example 3:
[0013] In this embodiment, the preparation process of nitrogen-doped molybdenum diselenide-coated carbon hollow spheres is the same as that in Example 1, except that the hydrothermal temperature, heating rate and calcination temperature are different. Specifically, the mixture of solution C and solution B is subjected to a hydrothermal reaction at 240°C for 12 hours; under an argon atmosphere, the temperature is raised to 600°C at a heating rate of 10°C / min for high-temperature calcination, and then cooled to room temperature to obtain black nitrogen-doped molybdenum diselenide-coated carbon hollow spheres. Similarly, the black nitrogen-doped molybdenum diselenide-coated carbon hollow spheres prepared in this embodiment are used as electroactive materials in 2016-type button batteries (one type of lithium-ion battery), and the assembly and performance testing methods are the same as in Example 1. Example 4:
[0014] In this embodiment, the preparation process of nitrogen-doped molybdenum diselenide-coated carbon hollow spheres is the same as in Example 1, except for the selection of alkylamine, hydrothermal temperature, heating rate, and calcination temperature. Specifically, 5.0 mL of ethylenediamine is mixed with solution A to form solution B; the mixture of solution B and solution C is subjected to a hydrothermal reaction at 220°C for 12 hours; under an argon atmosphere, the temperature is raised to 700°C at a heating rate of 5°C / min for high-temperature calcination, and then cooled to room temperature to obtain black nitrogen-doped molybdenum diselenide-coated carbon hollow spheres. Similarly, the black nitrogen-doped molybdenum diselenide-coated carbon hollow spheres prepared in this embodiment are used as electroactive materials in 2016-type button batteries (one type of lithium-ion battery), and the assembly and performance testing methods are the same as in Example 1. Example 5:
[0015] In this embodiment, the preparation process of nitrogen-doped molybdenum diselenide coated carbon hollow spheres is the same as in Example 1, except that the amount of vitamin C is different. Specifically, 0.5 g of vitamin C and 0.6523 g of molybdenum acetylacetonate are dissolved in 20.0 mL of deionized water under stirring to form solution A. Similarly, the black nitrogen-doped molybdenum diselenide-coated carbon hollow spheres prepared in this embodiment are used as electroactive materials in 2016-type button batteries (one type of lithium-ion battery), and the assembly and performance testing methods are the same as in Example 1. Please see Figure 6 , Figure 6 This is a GCD curve of the lithium-ion battery assembled with nitrogen-doped molybdenum diselenide-coated carbon hollow sphere electrodes in this embodiment at a current density of 1000 mA / g for different numbers of cycles. Figure 6 It can be seen that as the number of scans increases, the discharge specific capacity of the battery decreases slightly. Compared with the condition of using 1.0 gram of vitamin C in Example 1, the nitrogen-doped molybdenum diselenide-coated carbon hollow spheres prepared in this example have a larger discharge specific capacity. Example 6:
[0016] In this embodiment, the preparation process of nitrogen-doped molybdenum diselenide-coated carbon hollow spheres is the same as that in Example 5, except that the choice of alkylamine and the calcination temperature are different. Specifically, 5.0 mL of ethylenediamine is mixed with solution A to form solution B; under an argon atmosphere, the temperature is raised to 700 °C at a heating rate of 5 °C / min for high-temperature calcination, and then cooled to room temperature to obtain black nitrogen-doped molybdenum diselenide-coated carbon hollow spheres. Similarly, the black nitrogen-doped molybdenum diselenide-coated carbon hollow spheres prepared in this embodiment are used as electroactive materials in 2016-type button batteries (a type of lithium-ion battery), and the assembly and performance testing methods are the same as in Example 5. Example 7:
[0017] In this embodiment, the preparation process of nitrogen-doped molybdenum diselenide-coated carbon hollow spheres is the same as that in Example 5, except that the hydrothermal temperature, heating rate and calcination temperature are different. Specifically, the mixture of solution C and solution B is subjected to a hydrothermal reaction at 220°C for 12 hours; under an argon atmosphere, the temperature is raised to 600°C at a heating rate of 10°C / min for high-temperature calcination, and then cooled to room temperature to obtain black nitrogen-doped molybdenum diselenide-coated carbon hollow spheres. Similarly, the black nitrogen-doped molybdenum diselenide-coated carbon hollow spheres prepared in this embodiment are used as electroactive materials in 2016-type button batteries (a type of lithium-ion battery), and the assembly and performance testing methods are the same as in Example 5. Example 8:
[0018] In this embodiment, the preparation process of nitrogen-doped molybdenum diselenide-coated carbon hollow spheres is the same as in Example 5, except for the selection of alkylamine, hydrothermal temperature, heating rate, and calcination temperature. Specifically, 5.0 mL of ethylenediamine is mixed with solution A to form solution B; the mixture of solution B and solution C is subjected to a hydrothermal reaction at 240°C for 12 hours; under an argon atmosphere, the temperature is raised to 500°C at a heating rate of 5°C / min for high-temperature calcination, and then cooled to room temperature to obtain black nitrogen-doped molybdenum diselenide-coated carbon hollow spheres. Similarly, the black nitrogen-doped molybdenum diselenide-coated carbon hollow spheres prepared in this embodiment are used as electroactive materials in 2016-type button batteries (a type of lithium-ion battery), and the assembly and performance testing methods are the same as in Example 5.
Claims
1. A method for preparing nitrogen-doped molybdenum diselenide-coated carbon hollow spheres, characterized in that, The specific preparation steps are as follows: S1. Dissolve vitamin C and an organic molybdenum source in deionized water to form solution A, wherein the organic molybdenum source is molybdenum acetylacetonate; S2. Add an alkylamine to solution A obtained in S1 and mix to form solution B, wherein the alkylamine is either ethylenediamine or triethylamine; S3. At the same time, sodium selenite is dissolved in hydrazine hydrate to form solution C, wherein the molar ratio of sodium selenite to organic molybdenum source is 2:
1. S4. Add solution C obtained in S3 dropwise to solution B obtained in S2 and stir for 20 to 40 minutes to form a mixture. Then transfer the mixture to a hydrothermal reactor at 200 to 250°C and carry out a hydrothermal reaction for 10 to 14 hours. S5. After the hydrothermal reaction is complete, the product is naturally cooled to room temperature to obtain the hydrothermal product. The hydrothermal product is centrifuged, washed and dried to obtain a black precursor. S6. Place the black precursor obtained in S5 into a crucible and place it in the center of a tube furnace. Under an inert atmosphere, raise the temperature to 500-800℃ at a heating rate of 5-10℃ / min, hold at that temperature for 1.5-2.5 hours for high-temperature calcination, and then cool to room temperature to obtain black nitrogen-doped molybdenum diselenide-coated carbon hollow spheres.
2. The method for preparing nitrogen-doped molybdenum diselenide-coated carbon hollow spheres according to claim 1, characterized in that, In S5, the centrifugation speed is 5000-8000 rpm; washing is done by first washing with water and then washing with ethanol; the drying temperature is 50-80℃.
3. The method for preparing nitrogen-doped molybdenum diselenide-coated carbon hollow spheres according to claim 1, characterized in that, In S6, the inert gas is either nitrogen or argon.
4. The application of nitrogen-doped molybdenum diselenide-coated carbon hollow spheres prepared by the method for preparing nitrogen-doped molybdenum diselenide-coated carbon hollow spheres as described in any one of claims 1 to 3 in a 2016 coin cell, wherein the electrode of the 2016 coin cell comprises, by mass percentage, 70% nitrogen-doped molybdenum diselenide-coated carbon hollow spheres, 20% super-P and 10% polyvinylidene fluoride.
Citation Information
Patent Citations
Method for synthesizing molybdenum selenide / nitrogen doped carbon rod via solid-phase co-heating
CN109473634A
Porous carbon-loaded MoSe2 electrode material applied to lithium ion battery and preparation method thereof
CN112897479A
Preparation method of molybdenum diselenide-coated nitrogen-doped carbon nanotube composite material and lithium ion battery negative electrode material prepared from molybdenum diselenide-coated nitrogen-doped carbon nanotube composite material
CN115207305A
Molybdenum disulfide-carbon hollow sphere as well as preparation method and application thereof
CN112479258A
Preparation method and application of nitrogen-doped molybdenum diselenide hollow structure
CN117105183A